Surface morphology of worn out tool used for friction stir welding of aluminium plates by field emission scanning electron microscope (FESEM) - Ratnesh Kumar; Somnath Chattopadhyaya; Madhulika Srivastava; Saurabh Dewangan (Discover Applied Sciences)
Abstract Friction stir welding (FSW) is a solid-state joining technique that bonds materials without reaching their melting point. In this process, the tool plays a central role by generating the frictional heat necessary for welding, which directly influences weld quality, productivity, and production costs. This study focuses on analyzing both the temperature of the FSW tool and the wear it experiences during operation. The tool used in this investigation is made from SS410 stainless steel and is employed to weld AA 6061-T6 aluminum alloy under varying process parameters. Post-weld thermal imaging captures the temperature distribution of the tool, revealing a peak temperature of approximately 500 °C. Notably, the tool shoulder surface records the highest temperature during welding. To further understand wear mechanisms, a field emission scanning electron microscope (FESEM) is used to examine the wear patterns on the tool’s shoulder and pin. Several distinct wear sites are identified and subjected to detailed FESEM analysis. The results highlight that the tool shoulder surface endures the most significant wear due to direct contact with the workpiece material. Despite being originally designed with a narrow thread profile, the FESEM analysis reveals complete thread erosion during the welding process. Additionally, the tool shoulder edges exhibit pronounced damage resembling lightning strikes. The FESEM images also show crater formations, fractured surfaces, and surface delamination on the shoulder. This comprehensive study provides valuable insights into the complex wear behavior of FSW tools. The findings contribute to optimizing tool design and welding parameters, ultimately enhancing tool longevity and the overall efficiency of the welding process.